2007
DOI: 10.1111/j.1439-0264.2006.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AMH in Female Fetal Intersex Gonads in the Bovine

Abstract: Anti Müllerian Hormone, AMH, is believed to be the main agent in the freemartin syndrome. Supposing an active role of freemartin gonads in AMH secretion, in the present study, we aimed at investigating the presence and the localization of AMH producing cells either in fetal or in adult freemartin gonads. Our finding of positive AMH cells in a 26-week-old freemartin fetus indicates an active role of masculinized freemartin gonads in AMH secretion. However, the positive reaction, limited to few cells grouped in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
1
14
0
1
Order By: Relevance
“…This is essentially due to 2 different and sequential events: placental anastomosis occurring at 20-25 days of embryonic life, and sex differentiation occurring later (40-45 days) in cattle [Ruvinsky and Spicer, 1999]. This means that even if few male cells are present, the presence of male hormones, in particular AMH, affect internal sex female development [Ruvinsky and Spicer, 1999;Cabianca et al, 2007]. For this same reason, male freemartins are less exposed to sex damage, although some cases with reduced fertility have also been reported in freemartin males [Dunn et al, 1979;Gustavsson, 1980;Bongso et al, 1981;Seguin et al, 2000].…”
Section: Xx/xy Chimerismmentioning
confidence: 99%
“…This is essentially due to 2 different and sequential events: placental anastomosis occurring at 20-25 days of embryonic life, and sex differentiation occurring later (40-45 days) in cattle [Ruvinsky and Spicer, 1999]. This means that even if few male cells are present, the presence of male hormones, in particular AMH, affect internal sex female development [Ruvinsky and Spicer, 1999;Cabianca et al, 2007]. For this same reason, male freemartins are less exposed to sex damage, although some cases with reduced fertility have also been reported in freemartin males [Dunn et al, 1979;Gustavsson, 1980;Bongso et al, 1981;Seguin et al, 2000].…”
Section: Xx/xy Chimerismmentioning
confidence: 99%
“…Moreover, Echternkamp and Gregory [2002] suggested that it was not possible for single-born freemartins to occur. Generally, freemartins show progesterone levels <0.4 ng/ml [Cabianca et al, 2007]. In our case the level was higher (1.9 ng/ml), and the heifer was pregnant.…”
Section: Discussionmentioning
confidence: 87%
“…They possess bipotential genital ridges, Wolffian and Müllerian ducts, a urogenital sinus, a genital tubercle, and genital swellings [Lyle, 2007]. In XY embryos, Leydig cells within the testis secrete testosterone which promotes differentiation of the Wolffian duct into epididymis and vas deferens, whereas pre-Sertoli cells produce anti-Müllerian hormone (also called MIS for Müllerian inhibition substance) responsible for the degradation of the Müllerian ducts [Cabianca et al, 2007]. In XX individuals, the absence of testosterone and therefore dihydrotestosterone and MIS allows for the development of female internal and external genitalia.…”
Section: Discussionmentioning
confidence: 99%
“…Using a sensitive radioimmunoassay technique to quantify both serum and gonadal levels of AMH, Vigier et al [1984] showed that the regression of Müllerian ducts in freemartins is most likely induced by the AMH that is produced by the testes of the male twin. The capacity of some freemartin gonads to produce AMH has been demonstrated immunohistochemically by Cabianca et al [2007]. These authors showed that a few grouped cells located near testis cord-like structures were immunoreactive against a specific AMH antibody ( fig.…”
Section: Freemartinism In Bovids and Pigsmentioning
confidence: 99%